2021
DOI: 10.2147/dddt.s328371
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Drug Delivery Systems for Recurrent Aphthous Stomatitis

Abstract: Recurrent aphthous stomatitis (RAS) is a disease marked by painful oral lesions on the buccal and labial mucosa or tongue. Drug delivery systems (DDS) for RAS include topical forms that manage wound healing, cover the ulcer, and relieve the associated pain. DDS targeting the oral mucosa face a major challenge, especially the short residence times in the mouth due to the effect of “saliva wash-out”, which continually removes the drug. The objective of this review is to study the development of preparation forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 88 publications
(228 reference statements)
0
15
0
2
Order By: Relevance
“… (1) Surfactant (may act as a solubiliser, emulsifier, emulsion stabiliser, detergent, wetting agent, foaming agent/defoamer and may possess antimicrobial features) [ 75 ]; (2) mucoadhesive film former (filmogenic agents) (it is suggested that they may act as a moisturiser, as dressing for wounds, to prevent dental plaque and stain formation, to prevent demineralisation, as a barrier to relieve pain in oral lesions such as aphthous ulcers, to improving the delivery and retention of actives) [ 27 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]; (3) remineralisation agent (to remineralise the demineralised tooth surface in dental caries or erosion as well as to prevent demineralisation, also in dentin hypersensitivity to obturate the dentinal tubules); (4) antimicrobial agent (an oral antiseptic, it may act as a preservative); (^) means it is discussed in the subsequent text. …”
Section: Tablementioning
confidence: 99%
“… (1) Surfactant (may act as a solubiliser, emulsifier, emulsion stabiliser, detergent, wetting agent, foaming agent/defoamer and may possess antimicrobial features) [ 75 ]; (2) mucoadhesive film former (filmogenic agents) (it is suggested that they may act as a moisturiser, as dressing for wounds, to prevent dental plaque and stain formation, to prevent demineralisation, as a barrier to relieve pain in oral lesions such as aphthous ulcers, to improving the delivery and retention of actives) [ 27 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]; (3) remineralisation agent (to remineralise the demineralised tooth surface in dental caries or erosion as well as to prevent demineralisation, also in dentin hypersensitivity to obturate the dentinal tubules); (4) antimicrobial agent (an oral antiseptic, it may act as a preservative); (^) means it is discussed in the subsequent text. …”
Section: Tablementioning
confidence: 99%
“…Some studies have suggested that sodium alginate could treat recurrent aphthous ulcers. The compound can alleviate the pain and improve the persistence of a drug in the oral mucosa (Laffleur and Kuppers, 2019;Suharyani et al, 2021). In addition, alginate is mainly used for stomatology as an impression of oral materials (Cervino et al, 2018).…”
Section: Marine Algae Polysaccharidesmentioning
confidence: 99%
“…As lesões clássicas da EAR envolvem a mucosa oral não queratinizada, apresentando-se como úlceras rasas redondas ou ovais, dolorosas, claramente definidas, com um centro necrótico raso. O próximo passo é o estágio ulcerativo, no qual se desenvolve o edema, acompanhado pela presença de queratinócitos e vasculite superficial localizada, que gera inflamação na região, ulceração e infiltração de plasmócitos, linfócitos e neutrófilos (Gorsky et al, 2007;Suharyani et al, 2021). A resposta imune do hospedeiro leva as células T, macrófagos e mastócitos a liberarem o fator de necrose tumoral alfa (TNF-α), dando início ao processo de cicatrização (Cui et al, 2016).…”
Section: Estomatite Aftoide Recorrenteunclassified